Determinants of successful establishment and post‐translocation dispersal of a new population of the critically endangered St. Croix ground lizard (Ameiva polops). Issue 6 (14th July 2015) - Fitzgerald, Lee A.; Treglia, Michael L.; Angeli, Nicole; Hibbitts, Toby J.; Leavitt, Daniel J.; Subalusky, Amanda L.; Lundgren, Ian; Hillis‐Starr, Zandy
Abstract : Translocation to areas free of exotic predators, habitat degradation, or disease may be the most viable restoration option for many endangered species. We report on a successful translocation of the critically endangered St. Croix ground lizard, Ameiva polops, extirpated from St. Croix, U.S. Virgin Islands, Caribbean, by predation from introduced mongooses ( Herpestes auropunctatus ). We translocated 57 adult A. polops from Green Cay to Buck Island in May 2008. We placed 4 females and 3 males each in eight, 100 m 2, enclosures on Buck Island for 71 days, then the enclosures were opened. During the enclosure period, 20 individuals were identified and 32 others were seen. The average number sighted per survey was only 5.28 (range = 2–10). One hatchling was sighted in an enclosure, indicating a translocated female successfully nested. Body condition of the translocated individuals increased significantly by the end of the enclosure period. Population monitoring surveys at 61 sites across Buck Island showed that 5 years after the initial translocation in June 2013, the new population had grown to an estimated 1, 473 individuals and occupied 58.9% of the island. We attribute eradication of mongoose, life history of the species, large propagule size, condition of habitat, soft‐release, use of adults, interagency collaboration, and systematic assessment as primary factors that facilitated this successful translocation. Our findings provide meaningful insights on factors that enhance the potential for successful translocations, and point to new strategies aimed at restoring populations of endangered reptiles in their native ranges.